The Advice Prof. Dr. P.S. Van Koningsveld for the promotion of Dr.Machasin sept. 2, 1994 - Pieter Sjoerd van Koningsveld (Al-Jami'ah Research Centre, 1994)
Enough has been said already about all the technical details of your work, during your discussions with your supervisors, during the closed examination and also during this open, official ceremony. I am very grateful that you have also given me the opportunity to study your work and to give you, my remarks. Time will now come for you to prepare your work for its publication. This will give you the opportunity to think over everything that has been said and take it into account in one way or another. The INlS programme has already written to you that it is willing, in principle, to include your work in its printed series. When I try to do justice to the scope of your work, I would say that it contains two major axes or points of orientation. The first of these is the purely philological and historical approach. Your work mainly consists of an analysis of the methods or methodology applied by an important representative of one of the schools of Islamic theological thought, viz. Qādī 'Abd al-Jabbar al-Basrī. For this analysis, you base yourself on a number of ancient Arabic sources and, in doing so, you take into account the studies of other scholars, both from the Muslim world and the West. The publication and sources you have quoted in your thesis are mainly written in Arabic, English, French and German. This proves, I believe, that your main ambition and concern were to present a study. primarily concerned with the general history of Islamic thought taking into account the results of international scholarship.